Teatro científico : uma metodologia para o ensino de física - Fonseca, Sarah Suely Nascimento (2014)
In this research, the scientific theatre was used as a methodological proposal for the physics teaching in the second grade of high school of a school of integral education mode. The goal is to analyze if the theater as scientific methodology can help students learn better concepts of terminology, subject studied in the second grade of high school. Through theoretical and field research is observed that the concepts and standards worked rigidly and mechanized are not sufficient and not promote a satisfactory learning. Reflecting on this, is presented here a methodology that allows a physical learning that is important to the work and lives of students, favoring skills, knowledge and competencies that are attached to the pursuit of values, where the interpretation, performance and perceptions contributing to the moral and personal development. Is proposed theatre as artistic language articulator and interdisciplinary work with the various languages in the learning of scientific knowledge: history of physics, dance and parody. These were part of the actions related to the proposed approach. The results of the study have enabled dynamic teaching and learning activities and participation, which were regarded as relevant to the applicability in daily life of physics classes.